Implementation Of Local wisdom in Buffalo Raising in Musi Rawas Utara District - Hakim, Muhammad (Fapertago, 2023)
This study aims to determine the level of implementation of local wisdom in raising buffalo livestock in North Musi Rawas Regency. This study uses a survey method. The data collected consists of primary and secondary data. Data analysis used in this research is descriptive analysis. The results showed that breeders in North Musi Rawas Regency had implemented local wisdom values such as rearing buffalo with a rotating picket system 75.18%, Community buffalo rumble system 66.07%, Buffalo cattle belling (Neck tag) 69.64 %, and the construction of cages in groups (collectively) 63.39 %. Based on the description above, it can be interpreted that farmers in North Musi Rawas Regency have implemented local wisdom values in raising buffalo livestock so that they can support an increase in the buffalo population in North Musi Rawas Regency.